2006
DOI: 10.1016/j.ijsolstr.2005.04.017
|View full text |Cite
|
Sign up to set email alerts
|

A receding contact plane problem between a functionally graded layer and a homogeneous substrate

Abstract: In this paper, we consider the plane problem of a frictionless receding contact between an elastic functionally graded layer and a homogeneous half-space, when the two bodies are pressed together. The graded layer is modeled as a nonhomogeneous medium with an isotropic stress-strain law and over a certain segment of its top surface is subjected to normal tractions while the rest of this surface is free of tractions. Since the contact between the two bodies is assumed to be frictionless, then only compressive n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
44
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(49 citation statements)
references
References 25 publications
(28 reference statements)
3
44
1
Order By: Relevance
“…They can reduce the magnitude of residual and thermal stresses, mitigate stress concentration and increase fracture toughness [1]. In the past few years, many experimental and numerical results have shown that controlling a material property gradient in FGMs could lead to a significant improvement in the resistance to the contact deformation and damage [2][3][4][5][6][7][8][9][10][11][12]. This potential application motivates the study of the contact mechanics of FGMs.…”
Section: Introductionmentioning
confidence: 99%
“…They can reduce the magnitude of residual and thermal stresses, mitigate stress concentration and increase fracture toughness [1]. In the past few years, many experimental and numerical results have shown that controlling a material property gradient in FGMs could lead to a significant improvement in the resistance to the contact deformation and damage [2][3][4][5][6][7][8][9][10][11][12]. This potential application motivates the study of the contact mechanics of FGMs.…”
Section: Introductionmentioning
confidence: 99%
“…The case of anisotropy was investigated in papers [15]- [17], with particular reference to the results in [16] and [17], where the layer was modelled as a functionally graded material (FGM). Ahn and Barber investigated the case of frictional contact [18] under cyclic loading, but they used a uniformly distributed pressure of constant width.…”
Section: Introductionmentioning
confidence: 99%
“…Dag and Erdogan [13], Choi and Paulino [14] tackled the contact problem between a sliding rigid punch and a graded substrate with a surface/interface crack. Receding contact between a functionally graded coating and a homogeneous substrate as well as the partial slip contact problem was investigated by El-Borgi et al [15,16]. Wang et al analyzed systematically the plane [17], axisymmetric [18] contact problems of FGMs with a linear multilayered model.…”
Section: Introductionmentioning
confidence: 99%